Discharge summaries on a Paediatric Assessment Unit (PAU): how accurate are the medications on discharge when there has been no pharmacy involvement?. Issue 6 (9th May 2013) - Hibberd, S; Fox, A
Abstract : Introduction: The Paediatric Assessment Unit (PAU) sees approximately 600 patients each month with about three quarters being seen out of hours, (17:00–08:00 and weekends). During pharmacy hours, (08:30–17:00), the standard procedure is for the ward pharmacist to clinically screen each To Take Out (TTO) to ensure the choice of drug, its dose, frequency and formulation are correct and then make the supply. Aims: To determine the accuracy of prescribing and whether a supply has been appropriately made for all unscreened TTOs. Method: All TTOs are prescribed using E-docs, an electronic TTO system. All TTOs in June 2011 which were unscreened and contained medication were collected. The accuracy of these TTOs was cross checked with the patient notes, checks were made on the weight, allergy status and the patient's medication history. The nurses discharge section on PAU admission forms were also checked to confirm what the patient received. A prescribing error was defined as any unintended discrepancy between the intended prescription and the actual TTO. A supply error was defined as the patient not receiving the drug or being sent home with a drug inappropriately dispensed. Results: A total of 105 patients, (aged: 7 days–17 years), were discharged with medication without pharmacist involvement, 68, (65%), of these were out of hours. 43 TTOs, (41%), contained a total of 49 errors, a break-down of the error type revealed: duration 44.9%; supply 20.4%; frequency 14.3%; dose 12.3%; formulation 6.1% and strength 2%. Nineteen, (38.7%), of these errors were made in pharmacy hours and 55% of the total errors were made by SHOs which correlated to the proportion of TTOs that they wrote. Conclusions: 43 (41%) TTOs that were unscreened by a pharmacist left the hospital containing errors. 38.7% of these errors may have been avoided if the pharmacist had been contacted to provide a clinical screen. 26.5% of errors were due to no duration being indicated on the TTO at all, this was as a result of the 'From Ward' option being selected which then deletes the automatic prompt for a duration. 42% of TTOs that did not contain errors had the 'From Ward' option selected which meant the prescriber had to remember to put the duration in the management plan. PAU is a very busy environment with many distractions, the implementation of protected time when writing TTOs may see the error rate decrease. The introduction of 'order sentences' may prevent some drugs from being prescribed at the wrong time of day or with the wrong frequency. Feedback will be given to prescribers and training provided if prescribers feel that this may reduce the number of errors. Further research will be done into the prescribing abilities of new doctors and their understanding of the E-docs system. Nurses will be reminded of the procedures regarding supplying medication out of hours and given examples of what is and is not appropriate practice.